Strategi Optimalisasi Kebijakan Pengembangan Ekowisata di Jawa Barat - Maulana, Moch Rais; Nurpalah, Ahyan; Mafruhat, Ade Yunita (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
West Java has ecotourism potential that can improve the community's economy and regional income. This research aims to identify components and strategies that affect ecotourism, describe modeling using dynamic system analysis that can be a reference for predicting the future, as well as develop policies for the development of West Java Ecotourism Kesatuan Bisnis Mandiri (KBM). This research method uses a quantitative descriptive method. In this research, the author uses a dynamic system that can produce the right policy outlook in decision-making for 4 tourism components, which is expected to increase tourists and regional income. Based on the ecotourism KBM priority program, for tourism optimization there are three components that are focused on the categories of service improvement and comfort. From the results of the analysis, optimal strategies and policies are obtained, which can be assumed to have increased amenity by 8%, accessibility by 9%, and added an additional 3%.